2011
DOI: 10.1039/c1cs15046d
|View full text |Cite
|
Sign up to set email alerts
|

Structure:function relationships in molecular spin-crossover complexes

Abstract: Spin-crossover compounds are becoming increasingly popular for device and sensor applications, and in soft materials, that make use of their switchable colour, paramagnetism and conductivity. The de novo design of new solid spin-crossover compounds with pre-defined switching properties is desirable for application purposes. This challenging problem of crystal engineering requires an understanding of how the temperature and cooperativity of a spin-transition are influenced by the structure of the bulk material.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
852
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 823 publications
(886 citation statements)
references
References 313 publications
31
852
0
3
Order By: Relevance
“…In any case, however, the absence of any direct hydrogen bonding or strong - interactions between the iron centres in 1 and 2, and the increased rigidity of their lattices induced by Ag...Ag or Au...Au bonding, are both consistent with the observed poorly cooperative spin-crossover [35]. The gradual spin-crossover behaviour of 4 is less surprising, given the encapsulation of each cation by the anions in the lattice (Fig.…”
Section: Resultssupporting
confidence: 64%
“…In any case, however, the absence of any direct hydrogen bonding or strong - interactions between the iron centres in 1 and 2, and the increased rigidity of their lattices induced by Ag...Ag or Au...Au bonding, are both consistent with the observed poorly cooperative spin-crossover [35]. The gradual spin-crossover behaviour of 4 is less surprising, given the encapsulation of each cation by the anions in the lattice (Fig.…”
Section: Resultssupporting
confidence: 64%
“…The relationship between chemical structure and spin state is central to these phenomena 2, 11. A sterically crowded ligand sphere generally leads to high‐spin complexes 12.…”
mentioning
confidence: 99%
“…A possible approach to overcome this challenge consists of taking advantage of the sensitivity of spin-crossover complexes to subtle structural changes in metal coordination environments, which do not require magnetic cooperativity [13][14][15] . Thus, it has been shown that MOFs based on these molecular complexes exhibit magnetic switching at room temperature on physisorption of specific molecules within the porous framework 16,17 .…”
mentioning
confidence: 99%